2003
DOI: 10.1097/00001721-200312000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant activated factor VII for the treatment of life-threatening haemorrhage

Abstract: To describe the use of recombinant activated factor VII (rFVIIa) in patients with life-threatening haemorrhage. We report a case series of Australian patients with life-threatening haemorrhage who were treated with rFVIIa prior to August 2002 namely 21 patients, median age 45 years (range 22-79 years), 33% (seven of 21) female. The major causes for bleeding were multi-trauma, cardiac or vascular surgery, or orthoptic liver transplantation. In the 24 h prior to the administration of rFVIIa, the median blood usa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
0
3

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(63 citation statements)
references
References 17 publications
5
55
0
3
Order By: Relevance
“…The evidence on rFVIIa in refractory bleeding associated with cardiac surgery is currently limited to observational studies consisting of case reports (not referenced), case series, [27][28][29][30][31][32][33][34][35][36][37][38][39][40] and case-control studies. [41][42][43][44][45] These observational studies have important limitations such as reporting bias in favour of the intervention and inability to fully adjust for the effects of confounding variables.…”
Section: Rationalementioning
confidence: 99%
“…The evidence on rFVIIa in refractory bleeding associated with cardiac surgery is currently limited to observational studies consisting of case reports (not referenced), case series, [27][28][29][30][31][32][33][34][35][36][37][38][39][40] and case-control studies. [41][42][43][44][45] These observational studies have important limitations such as reporting bias in favour of the intervention and inability to fully adjust for the effects of confounding variables.…”
Section: Rationalementioning
confidence: 99%
“…The potential benefit of thrombelastography as a point-of-care tool in evaluation of dynamics of whole blood formation has been reported in a number of studies [3,4]. Recombinant activated factor VII (rFVIIa) has been reported as a potent and potentially useful haemostatic agent in the control of excessive bleeding in some traumatised patients [5,6]. Our laboratory has developed a thrombelastographic model of continuous whole blood coagulation, employing activation with minute amounts of tissue factor and novel data processing of the raw coagulation data signal to provide dynamic parameters of clot formation [7].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, other investigations performed in a rabbit model have indicated that colloid haemodilution may attenuate the haemostatic potential of rFVIIa [10]. In contrast, clinical experiences and several case reports point towards a beneficial effect of rFVIIa in control of massive bleeding with haemodilution by excessive use of volume substitution [6,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…For the last decade, the use of rFVIIa, with more specified data about mechanisms of its action has been successfully approved «off-label» to stop other uncontrolled hemorrhages unassociated with haemophilia, to reduce the need for allogenic blood. They included intracranial hemorrhage, bleedings due to coumarin use, hepatic coagulopathy, major surgery and traumas (Aggarwal et al, 2004;Aldouri, 2002;Dutton al., 2004;Eikelboom et al, 2003;Franchini et al, 2007;Ghorashian & Hunt, 2004;Hedner, 2003;Mathew, 2004;Martinowitz et al, 2002;Martinowitz & Michaelson, 2005;Mayo et al, 2004;Mittal & Watson, 2006;O'Connell et al, 2003;Price et al, 2004;Roberts et al, 2004;Sobieszczyk & Breborowicz, 2004;Uhlmann & Eby, 2004;Vincent et al, 2006).…”
Section: Indications and Clinical Situations For Rfviia Administrationmentioning
confidence: 99%
“…(Aggarwal et al, 2004;Ahonen & Jokela, 2005;Ahonen et al, 2007;Boehlen et al, 2004;Bomken et al, 2009;Bouwmeester et al, 2003;Boyer-Neumann et al, 2003;Brueckner et. al., 2001;Dart et al, 2004;Dutton et al, 2004;Eikelboom et al, 2003;Franchini et al, 2007;Franchini et al, 2008;Hollnberger et al, 2005;Holub et al, 2005;Jansen et al, 2005;Jimenez-Yuste et al, 2000;Kale et al, 2004;Kretzschmar et al, 2003;Macphail et al, 2004;Martinowitz & Michaelson, 2005;Mayo et al, 2004;Merchant et al, 2004;Mittal & Watson, 2006;Moscardo et al, 2001;Mousa & Walkinshaw, 2001;Mousa & Alfirevic, 2003,2007Nowacka et al, 2005;Palomino et al, 2006;Pepas et al, 2006;Price et al, 2004;Segal et al, 2004;Shamsi et al, 2005;Shander et al, 2005;Sobieszczyk et al, 2002Sobieszczyk et al, , 2004Sokolic et al, 2002;Tanchev et al, 2005;Verre et al, 2006;Vincent et al, 2006;Welsh et al, 2008;…”
Section: World Experience Of Use Of Rfviia In Treatment Of Pphunclassified